Mesoporous titania–vertical nanorod films with interfacial engineering for high performance dye-sensitized solar cells. (17th February 2015) - Ahmed, Irfan; Fakharuddin, Azhar; Wali, Qamar; Zainun, Ayib Rosdi Bin; Ismail, Jamil; Jose, Rajan
Abstract: Working electrode (WE) fabrication offers significant challenges in terms of achieving high-efficiency dye-sensitized solar cells (DSCs). We have combined the beneficial effects of vertical nanorods grown on conducting glass substrate for charge transport and mesoporous particles for dye loading and have achieved a high photoconversion efficiency of ( η ) > 11% with an internal quantum efficiency of ∼93% in electrode films of thickness ∼7 ± 0.5 μ m. Controlling the interface between the vertical nanorods and the mesoporous film is a crucial step in attaining high η . We identify three parameters, viz., large surface area of nanoparticles, increased light scattering of the nanorod–nanoparticle layer, and superior charge transport of nanorods, that simultaneously contribute to the improved photovoltaic performance of the WE developed.